Factors influencing intention of youth to donate blood: A case study at UiTM Melaka City Campus / Nurmazlina Mohd Isa and Siti Safwanah Misri - Mohd Isa, Nurmazlina; Misri, Siti Safwanah (Faculty of Administrative Science and Policy Studies, 2013)
Nothing is comparable to the preciousness of human blood. In this new era, although there are many modern and advance technology to produce something, but there is no factory that can manufacture blood. Human blood has no substitute. It is only in human beings that human blood is made and circulated. For those who are requiring blood for saving their lives, sharing from other family and fellows is the only means. Requirement of safe blood is increasing and regular voluntary blood donations are vital for blood transfusion services. Blood collection and transfusion are crucial to the functioning of a self-sufficient community based healthcare system in the Malaysia and the world.